Gig Economy: Unleashing the Potential of Digital Banking in Indonesia's Employment Regulations - Sudirman, Lu; Disemadi, Hari Sutra (University of Jember, 2023)
The gig economy has transcended mere trend status, emerging as a resilient force that promotes economies, even in the face of adversities like the COVID-19 pandemic. The gig economy not only impacts employment law but also intersects with regulations governing digital banking. Surprisingly, despite the exponential growth of gig workers in Indonesia, little attention has been given to comprehensively elucidating the legal interplay between employment law and digital banking. Therefore, this research aims to analyze the potential and legal challenges posed by the gig economy's development in the Indonesian economy. This research uses the Global South perspective as the gig economy offers unique challenges to an environment where issues in employment are already a problem. Furthermore, it examines the utilization of digital banking as a mechanism to address the pressing issues faced by gig workers. The potential limitation of this study is the lack of comprehensive data and empirical evidence, which may restrict the depth of analysis and the generalizability of the findings. The rationale of this legal study is to address the lack of comprehensive understanding regarding the legal interplay between employment law and digital banking in the context of the gig economy in Indonesia and bridge the gaps to connect these concepts under the legal context. Employing a normative legal research method with a statutory approach, this study offers a conceptual analysis of these intertwined concepts and their alignment with Indonesia's existing positive laws. The findings reveal significant connections between employment law and digital banking yet highlight the absence of well-defined legal boundaries within Indonesia's legal framework. Consequently, this research catalyses a novel branch of legal development in Indonesia, focusing on the gig economy and its profound implications.Keywords: Digital Banking, Employment Law, Gig Economy.